(Photo)electrocatalytic Versus Heterogeneous Photocatalytic Carbon Dioxide Reduction. Issue 9 (8th June 2021) - Bellardita, Marianna; Loddo, Vittorio; Parrino, Francesco; Palmisano, Leonardo
Abstract: The present review summarizes some of the main results achieved in electrochemical, photocatalytic, and (photo)‐electrocatalytic systems for the reduction of carbon dioxide. After a preliminary survey of the electrocatalytic and photocatalytic systems in terms of materials used, efficiencies, operating conditions, and product distribution, it is shown how the combination of the two approaches affords often higher efficiency than the single technologies and allows better control of the product distribution. In fact, the peculiar energetic distribution at the interface of irradiated semiconductors under opportune electrical bias enables enhancement of the spatial separation of the photogenerated charges and minimization of the external energy required in electrochemical applications. Even though the efficiency of CO2 reduction is still far away from being industrially appealing, in some cases the photoelectrocatalytic systems are promising tools to be further investigated for sustainable green chemistry based CO2 utilization. The aim of this review is to examine the strengths and the weaknesses of the different approaches considering that sometimes one of the three methods can be used more successfully than the others, depending on the desired product(s) and the materials used as photocatalysts or as the (photo)electrode. Abstract : Better together ? The electrocatalytic and photocatalytic reduction of carbon dioxide has been reviewed with the aim of examining strengths and weaknesses of the two methods. The synergism observed after the coupling of the two technologies allows in many cases to increase the process efficiency.